Irrigation development in Zimbabwe: understanding productivity barriers and opportunities at Mkoba and Silalatshani irrigation schemes - Moyo, Martin; Rooyen, Andre F. van; Chivenge, Pauline P.; Bjornlund, Henning (Informa UK Limited, 2017)
Productivity barriers and opportunities influencing smallholder irrigation sustainability in Zimbabwe were identified using case studies of the Silalatshani and Mkoba irrigation schemes. The major barriers were poor infrastructure and soil fertility, and poor access to farm inputs, farm implements, functioning markets and agricultural knowledge, which resulted in low yields, food insecurity and negative farm income. Most irrigated land remains unused, and marketing of produce is uncoordinated. Mobile technologies provide opportunities for market information dissemination. Institutions are needed to continuously encourage dialogue among agricultural value chain stakeholders to allow irrigators to align their operations to market demands and improve the viability of irrigation systems.